SENSITIVITY TO GENDER EQUALITY IN CITIES: THE SAMPLE OF WOMEN’S MARKET IN ALAPLI - HENDEN ŞOLT , H. Burçin (SSD Journal, 2021)
Although a balanced distribution is observed as the ratio of the female-male population in general, it is difficult to make a definite statement that there is a gender-based equality in issues such as access to services, participation in life, and active in politics. However, the issue of equality between men and women is the 10th issue of our Constitution. It is a right given to us in the article. A balance between the Sexes is necessary in access to public resources and, in particular, access to local urban services. Gender phenomenon is the study of the balance between the roles acquired by men and women in social terms and the rate of access to resources. Gender patterns formed by society affect women’s lives in urban spaces. With a system that leaves women in second place, it can create economic, cultural, educational and psychological effects in benefiting from urban services. The place of women in society may vary according to urban cultures. This study examines the interaction of urban culture and gender equality concepts. It is important for women to use urban spaces economically in the study of gender equality. There is a permanent Sunday place dedicated to women in Alaplı district of Zonguldak. A place in the history of urban culture, this Sunday is effective in terms of sensitivity to gender equality. The role of urban policies is great in the placement of the gender equality approach from local to national. The contribution of city governments to gender equality by bringing local values to the forefront will be positively reflected in women’s cultural and employment opportunities.